O Programa "Minha Casa, Minha Vida" na política habitacional brasileira: continuidades, inovações e retrocessos - Romagnoli, Alexandre José (2012)
This research aims to analyze the National Housing Policy of the Lula government throught the program Minha Casa, Minha Vida (PMCMV). The analizes concentrates on the continuities, innovations or any setbacks presents in PMCMV in comparison to Housing Policy historically built in Brazil. We assume that the housing issue is taken up in the country with the beginning of the Lula government, which shall enable a process of change in the area, such as the creation of a new Ministry (Ministry of Cities), changes in regulations sector, and programs with larger goals to those already found in the country. Implemented in this context that the PMCMV, although placed initially as a tool "anti-cyclical" government facing the international economic crisis, also stands outfor its social proposal. With the goal of building 1 million houses, being part of those destined for low-income population (historically one of the main bottlenecks Housing Policy) and considerable investment of resources of their own Federal Budget, the program becomes relevant and representative for the policy housing as a whole. From the neoinstitutionalist literature and public policy, this dissertation shows, in general, the PMCMV innovates with respect to funding issues and exploitation of the resources. The main result is the break with some logical housing production in the country, as the financing of housing policy from resources requiring immediate return, seeing a new trend in this direction. However, timidly intervenes in matters already well discussed in the country, such as urban planning and land tenure.